Respuesta :

Greetings!

Solve for a:
[tex]-8=a(2+5)^2+41[/tex]

Distribute the Parenthesis:
[tex]-8=(2a+5a)^2+41[/tex]

Apply the Exponent:
[tex]-8=(2a+5a)(2a+5a)+41[/tex]

Use Binomial Multiplication:
[tex]-8=2a(2a+5a)+5a(2a+5a)+41[/tex]

[tex]-8=(4a^2+10a^2)+(10a^2+25a^2)+41[/tex]

Combine Like Terms:
[tex]-8=4a^2+10a^2+10a^2+25a^2+41[/tex]

[tex]-8=49a^2+41[/tex]

Add -41 to both sides:
[tex](-8)+(-41)=(49a^2+41)+(-41)[/tex]

[tex]-49=49a^2[/tex]

Divide both sides by 49:
[tex] \frac{-49}{49}= \frac{49a^2}{49} [/tex]

[tex]-1=a^2[/tex]

Sqaure Root both sides:
[tex] \sqrt{-1}= \sqrt{a^2} [/tex]

[tex]-1=a[/tex]

[tex]a=-1[/tex]

The Answer Is:
[tex]\boxed{a=-1}[/tex]

I hope this helped!
-Benjamin